Analisis Nilai Tambah dan Efisiensi Proses Produksi Produk Olahan Jagung Sehat pada Kelompok Wanita Tani di Jeruklegi Wetan - Anisha Dian Iswahyuni (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Corn is a strategic agricultural commodity that contributes significantly to food security and economic development. Cilacap Regency, particularly Jeruklegi District, has considerable potential for corn production. However, the Wanasri Women Farmers Group (KWT) in Jeruklegi Wetan Village has not yet optimized corn utilization due to production and marketing constraints, resulting in limited value addition.This study aims to analyze the value added and production process efficiency of corn wonton chips as a healthy processed product to support the economic independence of women farmers. The study applies the Hayami value-added method and descriptive analysis to assess production efficiency. The findings show that processing 1 kg of corn into 15 packages of corn wonton chips generates an added value of IDR 98,500, with a value-added ratio of 54.72% and a profit rate of 49.16%. These results indicate that corn processing provides substantial economic benefits and is financially feasible. Improving production efficiency and cost control can further enhance profitability and sustainability. Overall, value-added processing of local corn has strong potential to increase income and strengthen the economic resilience of women farmers’ groups.